2016
DOI: 10.1002/ptr.5632
|View full text |Cite
|
Sign up to set email alerts
|

Potential Signaling Pathways Involved in the Clinical Application of Oxymatrine

Abstract: Oxymatrine, an alkaloid component extracted from the roots of Sophora species, has been shown to have antiinflammatory, antifibrosis, and antitumor effects and the ability to protect against myocardial damage, etc. The potential signaling pathways involved in the clinical application of oxymatrine might include the TGF-β/Smad, toll-like receptor 4/nuclear factor kappa-light-chain-enhancer of activated B cells, toll-like receptor9/TRAF6, Janus kinase/signal transduction and activator of transcription, phosphati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 64 publications
1
24
0
Order By: Relevance
“…Oxymatrine (OXY, Figure 1) is a quinolizidine alkaloid derived from Radix Sophora flavescens, and it possesses significant antioxidative and antiinflammatory activities via regulating several related signaling pathways (Liao et al, 2016;Lu, Xiang, & Xia, 2016;Ozturk, Cetinkaya, Yilmaz, & Ozturk, 2017;Zheng, Niu, Liu, Shi, & Lu, 2005). In the present study, we suspected that OXY has beneficial effects on gastric ulcers.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Oxymatrine (OXY, Figure 1) is a quinolizidine alkaloid derived from Radix Sophora flavescens, and it possesses significant antioxidative and antiinflammatory activities via regulating several related signaling pathways (Liao et al, 2016;Lu, Xiang, & Xia, 2016;Ozturk, Cetinkaya, Yilmaz, & Ozturk, 2017;Zheng, Niu, Liu, Shi, & Lu, 2005). In the present study, we suspected that OXY has beneficial effects on gastric ulcers.…”
mentioning
confidence: 72%
“…The use of medicinal plants or their derived active constituents that exhibit anti‐ulcer effects may be an alternative choice for the treatment of peptic ulcer disease in patients. Oxymatrine (OXY, Figure ) is a quinolizidine alkaloid derived from Radix Sophora flavescens , and it possesses significant antioxidative and antiinflammatory activities via regulating several related signaling pathways (Liao et al, ; Lu, Xiang, & Xia, ; Ozturk, Cetinkaya, Yilmaz, & Ozturk, ; Zheng, Niu, Liu, Shi, & Lu, ). In the present study, we suspected that OXY has beneficial effects on gastric ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…Its molecular formula is C 5 H 24 N 2 O 2 , and it is a hydrophilic monomer. 3 Some research has shown that oxymatrine has anti-tumor effects in breast cancer, non-small-cell lung cancer, cervical cancer, and bladder cancer cells. [4][5][6][7] Oxymatrine can inhibit the proliferation and migration of tumor cells by inhibiting the p38, EGFR/ PI3K/AKT/mTOR, and MEK-1/ERK1/2/MMP2 signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Oxymatrine (OMT), one of the main bioactive ingredients of Sophorae flavescentis radix, which is known as a traditional Chinese herbal medicine extracted from the dried root of Sophorae flavescens Aiton [14,15]. Previous studies have demonstrated that OMT shows a wide-range of pharmacological effects, including anti-inflammatory, anticancer, antiviral and immunomodulatory effects [14,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that OMT shows a wide-range of pharmacological effects, including anti-inflammatory, anticancer, antiviral and immunomodulatory effects [14,[16][17][18][19]. In recent years, the cardio-protective effects of OMT are becoming more and more arresting, and it has been used to treat cardiovascular diseases via anti-arrhythmic effect, vasodilative activity, hypolipidemic, positive inotropic effect and resistance of ventricular remodeling [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%